The Impact of Long-Term Nitrogen Addition on Microbial Community Composition in Three Hawaiian Forest Soils - Teri C. Balser (The Scientific World Journal)
We evaluated the microbial communities in three Hawaiian forest soils along a natural fertility gradient and compared their distinct responses to long-term nitrogen (N) additions. The sites studied have the same elevation, climate, and dominant vegetation, but vary in age of development, and thus in soil nutrient availability and nutrient limitation to plant growth. Fertilized plots at each site have received 100 kg ha year-1 N addition for at least 8 years. Soil parameters, water content, pH, and ammonium and nitrate availability differed by site, but not between control and N-addition treatments within a site at the time of sampling. Microbial biomass also varied by site, but was not affected by N addition. In contrast, microbial community composition (measured by phospholipid analysis) varied among sites and between control and N-addition plots within a site. These data suggest that microbial community composition responds to N addition even when plant net primary productivity is limited by nutrients other than N. This may have implications for the behavior of forests impacted by atmospheric N deposition that are considered to be “nitrogen saturated,” yet still retain N in the soil.